Pengalaman Psikososial Penderita Systemic Lupus Erythematosus: A Systematic Review - Sahrir Ramadhan; Tintin Sukartini; Ferry Efendi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: Systemic lupus erythematosus usually affects many organ systems including the central nervous system. So that it can cause several neuropsychiatric syndromes, including depression. In addition, lupus patients also experience frustration and social stress such as loss of the ability to work which results in unemployment resulting in reduced income from lupus sufferers and limitations in social interactions which are also major problems. Objective: to determine the psychosocial experiences of people with systemic lupus erythematosus. Methods: The databases used in this study were Scopus and Proquest, limited to publications for the last 15 years from 2005 to 2020, full text articles and in English. The keywords used are "lupus", "SLE", "Systemic Lupus Erythematosus", "psychology", "social", "psychosocial". This systematic review uses 10 articles that fit the inclusion criteria. Results: From 10 articles, it was found that the psychosocial experiences experienced by people with systemic lupus erythematosus affected how the quality of life of the sufferer. Social support positively influences the physical and psychological components of the quality of life of patients with systemic lupus erythematosus. Neglected depression and anxiety issues can not only reduce quality of life, but also create intense anxiety including suicidal ideation. Conclusion: Psychosocial experiences experienced by people with systemic lupus erythematosus will affect the quality of life of the sufferer. Positive psychological responses and strong social support can improve the quality of life for people with systemic lupus erythematosus. Keywords: psychosocial; systemic lupus erythematosus; quality of life ABSTRAK Latar belakang: Systemic Lupus Erythematosus biasanya mempengaruhi banyak sistem organ tubuh termasuk system saraf pusat. Sehingga dapat menyebabkan beberapa sindrom neuropsikiatri, termasuk depresi. Selain itu pasien lupus juga mengalami frustasi dan stress sosial seperti kehilangan kemampuan untuk bekerja yang menyebabkan tidak adanya pekerjaan sehingga pendapatan dari penderita lupus berkurang dan keterbatasan dalam interaksi sosial yang juga merupakan masalah utama. Tujuan: untuk mengetahui pengalaman psikososial penderita systemic lupus erythematosus. Metode: Database yang digunakan dalam penelitian ini adalah Scopus dan Proquest terbatas untuk publikasi 15 tahun terakhir dari 2005 hingga 2020, full text article dan berbahasa Inggris. Kata kunci yang digunakan adalah “lupus”, “SLE”, “Systemic Lupus Erythematosus”, “psychology”, “social”, “psychosocial”. Systematic review ini menggunakan 10 artikel yang sesuai dengan kriteria inklusi. Hasil: Dari 10 artikel didapatkan hasil bahwa bahwa pengalaman psikososial yang dialami oleh penderita systemic lupus erythematosus mempengaruhi bagaiamana kualitas hidup dari penderitanya. Dukungan sosial mempengaruhi secara positif komponen fisik dan psikologis dari kualitas hidup pasien systemic lupus erythematosus. Masalah depresi dan kecemasan yang diabaikan tidak hanya dapat mengurangi kualitas hidup, tetapi juga menciptakan kegelisahan yang hebat termasuk ide bunuh diri. Simpulan: Pengalaman psikososial yang dialami penderita systemic lupus erythematosus akan mempengaruhi kualitas hidup penderitanya. Respon psikologis yang positif dan dukungan sosial yang kuat dapat meningkatkan kualitas hidup penderita systemic lupus erythematosus. Kata kunci: psikososial; systemic lupus erythematosus; kualitas hidup